Nuclear Threat in Africa: What Option for Nigeria. - Oyedepo, Hezekiah Bamidele Olatunji (Obafemi Awolowo University, 2014)
Africa was left out of nuclear debate until recently today; South Africa is known to have engaged in a lot of nuclear activities. This development has generated some concern in Africa because it is seen as a ploy to delay the achievement of self-termination, political independence, and majority rule within African continent - a region Nigeria seeks to lead. This study examines the development of nuclear capabilities in Africa, particularly South Africa; the amount of threat the South African clear facilities generate in Nigeria; and Nigeria's option in the face of the apparent nuclear threat in Africa.